A alteridade docente: uma cartografia da subjetividade do professor readaptado - Vidal, Emerson Pessoa (2020)
The teaching function is something of a unique nature and has been gradually undergoing profound changes in the globalized world. Sometimes, these changes that reflect society, are bringing to education professional a new context in which their participation can be permeated by suffering and corrosion of relationships. In order to investigate the readapted teacher, this work set out to investigate the subjectivity of such a professional, who interspersed with different ways in dealing with the instability that befell the teacher when he was overwhelmed by activities and relationships between school / teacher and student / teacher who wore oust and started to instill anguish in such professionals. That is how we sailed towards an experience that would allow us to see the reality of the readapted teacher, as well as the agency of new rhizomatic connections and exploring new territories beyond that in which they were temporarily occupying. It was in this sense that the objective was to provide a mutability of multiplicities that would allow, at the same time, to find and follow deterritorializing paths, and to make new connections with the non-instituted. It was noticed that the readapted teacher finds three ways to deal with the instability that disorganizes his territories and that in turn cause more or less anguish, depending on the context and the vital forces that each subject carries within him. Although the school claims to want the proactive professional, in reality what it wants is the resigned professional and standard model. In such a way, it is realized that the extracognitive experience must be emphasized so that professionals can have resonance with other bodies and thus have good meetings that promote the increase of vital power